Taxonomic confirmation of Gelidium americanum (Gelidiaceae, Rhodophyta) in Tabasco, Mexico, using a morphological and molecular approach - Quiroz-González, Nataly; Rivas Acuña, Ma. Guadalupe; Ponce Márquez, Ma. Edith (Instituto de Ecología, A.C., 2021)
Background and Aims: Gelidium americanum is widely distributed on the Atlantic coast of Mexico; however, so far no studies have been conducted to confirm its taxonomic identity using molecular markers and morphological characters. The objective of this study was to confirm the taxonomic identity, with a morphological and molecular approach, of the specimens identified as G. americanum previously collected in the coastal lagoon of Mecoacán, Tabasco, Mexico.Methods: Three specimens of G. americanum were collected in the Mecoacán lagoon, Tabasco, Mexico. The material was morphologically analyzed by observations with stereoscopic and optical microscopes. For molecular analysis, DNA was extracted from the samples using the CTAB method; rbcL and COI-5P markers were amplified with the Phire Plant Direct kit (PCR), the sequences were edited in Bioedit and aligned in Clustal W. Next, a Maximum Verisimilitude analysis was done in RaxML, a Bayesian Inference analysis in MrBayes, and genetic distances were calculated in MEGA.Key results: The sequences obtained in the present study for rbcL and COI-5P markers were nested in the clade of samples previously identified with molecular markers as Gelidium americanum. In addition, genetic distances were minimal, the morphological characters coincided with what was previously described for other locations in the Atlantic, despite having a limited number of specimens.Conclusions: Using molecular markers and morphological characters, the presence of Gelidium americanum in the Mecoacán lagoon is confirmed despite having different environmental characteristics to those that have usually been described for this species.